1998
DOI: 10.3109/08880019809167229
|View full text |Cite
|
Sign up to set email alerts
|

BCL-2 Expression and Prognosis in Childhood Acute Leukemia

Abstract: Bcl-2 expression and its prognostic value were evaluated in 42 children with acute leukemia. The Bcl-2 expression of the leukemic blast cells was measured quantitatively by flow cytometry and was further analyzed by the simultaneous immunostaining of Bcl-2 with the surface membrane antigens, DNA, Ki-67 antigen. All of the cases showed a consistent expression of Bcl-2 protein; virtually all leukemic lymphoblasts were Bcl-2 positive. Although the expression of Bcl-2 varied widely from 7 to 80 x 10(3) MESF units,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…15,34 Furthermore, it has been shown that relapsed ALL cells are more resistant to various drugs, such as glucocorticoids, l-asparaginase, anthracyclins, and thiopurines 35 and more frequently exhibit reduced apoptosis than newly diagnosed ALL. 36 We therefore investigated the Bax-␣ and Bcl-2 levels in lymphoblasts at first presentation and relapse from patients with childhood ALL.…”
Section: Discussionmentioning
confidence: 99%
“…15,34 Furthermore, it has been shown that relapsed ALL cells are more resistant to various drugs, such as glucocorticoids, l-asparaginase, anthracyclins, and thiopurines 35 and more frequently exhibit reduced apoptosis than newly diagnosed ALL. 36 We therefore investigated the Bax-␣ and Bcl-2 levels in lymphoblasts at first presentation and relapse from patients with childhood ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the predictive value of the expression level of various Bcl-2 family members in ALL at diagnosis. [35][36][37][38][39][40][41][42][43][44][45] The majority of these studies indicate that steady-state levels of individual Bcl-2 family members are not optimal predictors of outcome 35,36,38,39 or ex vivo GC-sensitivity. 37,40,42 On the other hand, several studies using cell viability assays have demonstrated that ex vivo GC-sensitivity has a predictive value in relation to the short-term response to systemic GC monotherapy and to the long-term clinical outcome in response to combination chemotherapy.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…21 Several attempts have been made to correlate expression levels of resistance genes with clinical outcome of leukemia. 14,[22][23][24][25] Only a few studies have assessed the association between candidate gene expression and survival in acute myelogenous leukemia (AML), most of them with rather small patient numbers, and sometimes with conflicting results. 9,22,26,27 Therefore, the potential prognostic value of apoptosis-related genes in AML remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…14,[22][23][24][25] Only a few studies have assessed the association between candidate gene expression and survival in acute myelogenous leukemia (AML), most of them with rather small patient numbers, and sometimes with conflicting results. 9,22,26,27 Therefore, the potential prognostic value of apoptosis-related genes in AML remains to be elucidated. In this retrospective analysis, we used a semi-automated highthroughput methodology to study the expression of apoptosisrelated genes (Mdm-2, Bcl-2, Bcl-x L , Bad, Bax) in 232 AML specimens and correlated expression with response to ICT and survival.…”
Section: Introductionmentioning
confidence: 99%